Development of microfluidic gradient generator for bio-applications - Andrew Santoso (2013)
Microfluidic gradient generators are being developed for combinatorial and concentration-dependent studies. It is advantageous for biological applications because it eliminates the use of large amount of expensive reagents and gives higher throughput.